ECONOMIC COOPERATION BETWEEN UZBEKISTAN AND AZERBAIJAN IN THE 21ST CENTURY - Islomov Abdulaziz Latif o’g’li; Shariboev Abdurakhmon Abduqodir ogli (Bright Mind Publishing, 2025)
This article analyzes the issues of economic cooperation between Uzbekistan and Azerbaijan in the 21st century. Dedicated to the analysis of the development processes, directions and prospects of economic cooperation between Uzbekistan and Azerbaijan in the 21st century. The article examines key aspects of the historical, cultural and economic ties between the two countries and analyzes how they are developing in the modern global and regional economic environment. Historical roots, cultural cohesion and economic interests uniting Uzbekistan and Azerbaijan serve as the basis for further strengthening cooperation. In the 21st century, these ties are rising to a new level of quality, with large-scale cooperation projects in areas such as transport, energy, agriculture, investments and trade
Keywords: Uzbekistan, Azerbaijan, Energy Security, Organization of Turkic states, Shanghai Cooperation Organization.